Moving beyond the toolbox: Providing social movement studies with a materialist dialectical lens - Engelhardt, Anne; Moore, Madelaine (Momentum Quarterly, 2017)
Numerous studies within critical political economy try to make sense of the (post-)crisis period by focusing on top-down analyses of capitalist hegemony. They appear to ignore the proliferation of social movements that emerged in that period. In contrast, social movement studies tend to lack a theory of capital and thus, missing the class struggle, inadequately addresses questions of the state, power relations, and what movements may mean for our current capitalist conjuncture. To provide an analysis that can benefit from both traditions, we propose to re-embed methods employed by key social movement scholars such as Charles Tilly, Doug McAdam and Sidney Tarrow into a critical social theory centred on class struggle, by a non-dogmatic use of a materialist dialectical lens. Consequently, cognitive, relational, and environmental mechanisms are repurposed as cognitive, organizational, environmental, and institutional dynamics. This reformulation focuses on processes and relations rather than inputs and outputs (failure/success), or static categories, which tend to dominate social movement studies.